2019
DOI: 10.1111/1751-7915.13391
|View full text |Cite
|
Sign up to set email alerts
|

Lime and ammonium carbonate fumigation coupled with bio‐organic fertilizer application steered banana rhizosphere to assemble a unique microbiome against Panama disease

Abstract: Summary Microbiome plays a key role in determining soil suppressiveness against invading pathogens. Our previous study revealed that microbial community of bulk soil could be manipulated by lime and ammonium bicarbonate fumigation followed by biofertilizer application. However, the assembly of microbial community suppressive to banana Panama disease in the rhizosphere is still unclear. In this study, we used high‐throughput sequencing and quantitative PCR to explore the assembly of rhizosphere micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…can promote plant growth, P solubilization, N fixation and overall plant productivity (Antoun et al, 1998;Avis et al, 2008). It is now well established that biofertilizers can have an impact of the rhizospheric community and agricultural plant productivity (Trivedi et al, 2017;Shen et al, 2019;Thomashow et al, 2019). In fact, plants and microbes should likely be redefined as holobionts, an assemblage of different species that forms an ecological unit (Margulis and Fester, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…can promote plant growth, P solubilization, N fixation and overall plant productivity (Antoun et al, 1998;Avis et al, 2008). It is now well established that biofertilizers can have an impact of the rhizospheric community and agricultural plant productivity (Trivedi et al, 2017;Shen et al, 2019;Thomashow et al, 2019). In fact, plants and microbes should likely be redefined as holobionts, an assemblage of different species that forms an ecological unit (Margulis and Fester, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the effects of ANE on plant development, the effect of seaweed extracts on the biology of the rhizosphere is still largely unknown. Yet, previous work has showed that the application of biofertilizer (containing fermented Bacillus and pig manure) can reshape the rhizosphere community and may help to control diseases (Shen et al ., , ). The rhizosphere harbours a large microbial biodiversity where numerous microbial taxa form biofilm that contributes to the aggregation of particles, enhances nutrient cycling and delivery to plants, degrades toxic substances, allows better soil water retention and plays a role in plant disease management (reviewed by Pandin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the environmental disturbances experienced by many soil communities, disturbances often arise from different land use management regimes and associated practices 4 . Fumigation, a widely used practice for suppressing soil-borne diseases 6 , 7 , especially fungal pathogens 8 , represents a drastic disturbance to the soil microbiome 9 , 10 . However, fumigation often leads to transient disease suppression as soils experience rapid pathogen reinfestation 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, microbial biomass that is not dried and mostly viable, a so‐called biofertilizer, is known to perform indirect fertilization (e.g. biological N 2 fixation), or possess bioactive compounds to promote plant growth and health (Shen et al , 2019; Sakarika et al , 2020). It is currently unknown whether bioactive compounds remain present and active after drying, and this research line should be further explored to include all growth‐promoting effects.…”
Section: Discussionmentioning
confidence: 99%